Influence of Provision of Teaching and Learning Resources on Academic Performance in Public Secondary Schools in Kisii Central Sub-County, Kenya - Mongare Babu; Dr. Christopher Ayienda (IJRDO- Journal of Educational Research, 2020)
Establishment of Boards of Management in secondary schools is to enhance professionalism in the management of the public secondary schools. The study sought to carry out an assessment of influence of provision of teaching and learning resources on academic performance in public secondary schools in Kisii Central Sub-County, Kenya. A mixed methods approach was applied together with the concurrent triangulation research design which entailed a fusion of data from quantitative and qualitative sources. The target population was 498 respondents made up of 45 Principals, 450 BOM members, 1 the Sub County Director of Education, 1 quality control and standards officer and 1 curriculum support officer. The principal, Sub- County director of Education, Curriculum support officer and DQSO were sampled purposively including the Bom chairmen in each of the 45 schools. Data was collected by use of questionnaires for the principals and interview guides for BOM Members and Sub- County director, CSO and DQSO. Piloting of the research instruments was done on 10% of the sample size in Kisii North Sub- County. Validity of instruments was tested using content validity while reliability of instruments was tested using test re-test technique and Cronbach’s alpha method of 0.75 was used to calculate the internal efficiency. Credibility of the data was tested using data triangulation through multiple analysis while dependability of data was assured through reporting data collection process in details. Qualitative data was analyzed in narrative form while quantitative data was coded and entered in to Statistical Package for Social Sciences (SPSS) version 23.0 to produce both descriptive and inferential statistics. Descriptive statistics were analyzed to find mean, mode and standard deviation while on the other hand inferential statistics was analyzed in form of correlation, regression and analysis of variance (ANOVA). Most of the respondents confirmed that a program of events that is adhered to enabled provision of the required teaching and learning materials in their schools. Most of the respondents were of the view that BOM members can effectively make forecast and budget for physical facilities independently. All the respondents confirmed that individuals serving in BOM had high standards of moral and social probity and could be trusted with incentives by the community. The study recommended that: -The Ministry of Education should put in place measures to ensure that only competent persons sit on the Boards of Management of the public secondary schools.